Selective Suppression of Prevotella and Modulation of Oral Dysbiosis in Stunted Children: The Role of Systemic Zinc as a Biological Adjuvant to Mechanical Therapy - Nila Kasuma; Dewa Made Wedagama; Thifla Rafifa Wirza; Dedi Sumantri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Gingivitis in stunted children represents a unique pathological entity driven by a compromised mucosal barrier and systemic zinc deficiency. These children exhibit a phenotype of acquired immunodeficiency, where standard mechanical debridement often fails to resolve inflammation, leading to a phenomenon known as dysbiotic rebound. This study investigated the biomolecular efficacy of systemic Zinc supplementation combined with scaling and root planing (SRP) in modulating the oral microbiome of nutritionally vulnerable children. Methods: A randomized, single-blind, pre-post test controlled clinical trial was conducted in Padang, Indonesia, involving 30 stunted children (Height-for-age Z-score < -2 SD) diagnosed with generalized gingivitis. Participants were randomized into a Control group (SRP + Placebo, n=15) and an Intervention group (SRP + 20mg Zinc Sulfate Monohydrate daily, n=15) for a duration of 14 days. Microbial profiling was performed on unstimulated saliva utilizing high-throughput 16S rRNA gene sequencing (V3–V4 region). Bioinformatics processing utilized the DADA2 pipeline to generate Amplicon Sequence Variants (ASVs). Results: Results indicated that SRP alone resulted in a pathogenic recolonization dominated by Firmicutes (+49.6%). Conversely, Zinc supplementation induced a significant Gram-negative crash, reducing Proteobacteria by 50.6%. Most notably, the key periodontal pathogen Prevotella was suppressed to undetectable levels in the Zinc group (p<0.05). Conclusion: Systemic zinc acts as a potent biological scaffold in the enterosalivary cycle, likely repairing the epithelial barrier and starving hemin-dependent pathogens. It is strongly recommended as a therapeutic adjuvant to prevent the ecological recurrence of gingivitis in nutritionally vulnerable pediatric populations.